Braincase of Siamraptor suwati and insights into the cranial anatomy of Carcharodontosauria - Soki Hattori; Duangsuda Chokchaloemwong; Soichiro Kawabe; Elena Cuesta; Masateru Shibata; Kazunori Miyata; Yoichi Azuma (PLoS ONE, 2026)
Two partial theropod braincases, namely NRRU-F01020035 and F01020036, were recovered from the Lower Cretaceous Khok Kruat Formation in Nakhon Ratchasima, Thailand. Detailed observations on these two specimens revealed their carcharodontosaurian affinity based on the presence of several synapomorphies for the clade, such as partially-roofed anteromedial corner of the supratemporal fossa and a tall nuchal crest. In combination with the monospecific occurrence of Carcharodontosauria in the locality, both specimens can be attributed to Siamraptor suwati , although such braincase preserving the synapomorphic characters has been unknown in this taxon so far. In addition, the wedge-shaped frontoparietal suture and two deep pits on the lateral margin of the frontal shared in the two braincases, which have not been reported in any allosauroid, are shared by both specimens and thus can be regarded as additional autapomorphies of Siamraptor . The phylogenetic analysis incorporating information from the braincases confirmed the position of Siamraptor as an earliest-branching member of Carcharodontosauria as discussed in the original description, and further comparison with other allosauroid braincases revealed several aspects of the evolutionary history of carcharodontosaurian characters.